Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1971
DOI: 10.1128/jb.106.2.626-633.1971
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Association of Conjugally Transferred Deoxyribonucleic Acid in Escherichia coli Minicells

Abstract: The conjugally acquired deoxyribonucleic acid (DNA) of small, anucleate cells (“minicells”) of a mutant strain of Escherichia coli K-12 was found to be predominantly associated with the bacterial membrane. Evidence from X-irradiation studies in vivo shows that there is no decrease in DNA-membrane association under conditions which reduce the DNA to one-sixth its original size and suggests the possibility of multiple DNA-membrane association sites. Preliminary enzymatic studies indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1972
1972
1975
1975

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…By using X rays to introduce double-strand breaks in DNA, Burrell et al (5) concluded that the chromosome of Micrococcus radiodurans has one or two membrane attachment points. Shull et al (35) reported that episomal DNA introduced conjugally into E. coli minicells is attached to the membrane at many points.…”
mentioning
confidence: 99%
“…By using X rays to introduce double-strand breaks in DNA, Burrell et al (5) concluded that the chromosome of Micrococcus radiodurans has one or two membrane attachment points. Shull et al (35) reported that episomal DNA introduced conjugally into E. coli minicells is attached to the membrane at many points.…”
mentioning
confidence: 99%
“…An analysis of the molecular weights of DNA transferred to Eex+ and to Eexrecipients was undertaken to investigate this possibility. Shull et al (27) have reported that DNA transferred from Hfr donors to F-minicells has a weightaverage molecular weight of 20 x 106 to 30 x 10! We measured the molecular weights of DNA transferred from Hfr and R+ donors to excluding and nonexcluding minicell recipients.…”
Section: Resultsmentioning
confidence: 99%
“…Conflicting evidence of "membrane-attachment" has been reported using a different method of preparation (the M' band method [226]-by direct lysis of lysozyme-EDTA spheroplasts with Sarkosyl on sucrose gradients. DNA in minicells derived from an R factor, or from F ColV ColB trp cys (neither plasmid investigated in "cleared lysates") or from an F+ parent was concluded to be membrane associated from its co-sedimentation with the M band (213).…”
Section: Discussionmentioning
confidence: 99%